Stabilization of peat soil using fly ash, bottom ash and portland cement: soil improvement and coal ash waste reduction approach - Hauashdh, Ali; Radin Mohamed, Radin Maya Saphira; Jailani, Junaidah; Abd Rahman, Junita
Peat soil is very compressible, which leads to an excessive settlement. Stabilization of peat soil is the way to improve the engineering properties of peat soil through mixing peat with supplementary cementation materials. Therefore, this study aims to investigate the stabilization of peat soil using fly ash, bottom ash and ordinary Portland cement (OPC) to improve the engineering properties of peat soil. Also to examine the possibility of fly ash and bottom ash waste reduction through using them as a binder of the mixture in soil improvement application. In this study, fly ash and bottom ash were collected from generation wastes at coalfired electric power and stabilization of peat soil was done by mixing peat soil with fly ash, bottom ash and OPC. Unconfined compressive strength (UCS) and Fourier transform scanning electron microscope (FESEM) was conducted before and after the stabilization of peat soil. Also, some essential physicochemical properties of a mixture have identified before the mixing process. The findings of the compressive strength of peat soil were equal to 5 kPa at its natural state and after stabilization strength of peat soil was equal to 47 kPa. FESEM micrographs have shown ultrastructure of peat stabilization appears as inherent and coherent while the ultrastructure of original peat appears as incoherent and sporadic. The findings have revealed the effectiveness of fly ash and bottom ash to improve the strength of peat and the applicability of the utilization of coal ash waste as binder materials.